The Geographical Distribution of Human Cutaneous and Visceral Leishmania Species Identified by Molecular Methods in Iran: A Systematic Review With Meta-Analysis - Hajjaran, Homa; Saberi, Reza; Borjian, Alireza; Fakhar, Mahdi; Hosseini, Seyed Abdollah; Ghodrati, Sajjad; Mohebali, Mehdi (Frontiers in Public Health, 2021)
Leishmaniasis is one of the most common vector-borne parasitic diseases in Iran. Leishmania species identification is necessary for epidemiological aspects, precise prognosis, control and treatment of the disease. We systematically searched all the studies, reports and documentation related to species identification and geographical distribution of causative agents of cutaneous (CL), mucosal (ML) and visceral leishmaniasis (VL) using DNA-based molecular diagnostic techniques in Iran. International databases including PubMed, ScienceDirect, Embase, Google Scholar, Scopus, and Web of Science were systemically searched for English articles and Iran’s databases including SID, IranMedex and Magiran were searched for Persian reports and articles. Searches were performed from 1999 to 2019 (20 years). The current review was conducted using the keywords: cutaneous leishmaniasis, visceral leishmaniasis, Leishmania species, Human, Molecular, PCR, and Iran. The study quality was evaluated using the NOS checklist. This meta-analysis procedure was accomplished using STATA, version 2.7.9. Of the 3426 records identified in the initial search, 154 articles met inclusion criteria and qualified for the systematic review and meta-analysis. In subgroup analysis, the pooled frequency of causative agents of CL isolates was 67.3% (95% CI: 59.51 – 74.67%) for L. major and 32.1% (95% CI: 24.72- 39.87%) for L. tropica. In addition, the pooled frequency of causative agents of VL isolates was 97.1% (95% CI: 94.6– 98.8%) for L. infantum and 2.9% (95% CI: 1.12-5.37%) for L. tropica. The findings of this study showed that the main causative agents of CL and VL in Iran are L. major and L. infantum, respectively. Moreover, kinetoplast DNA (kDNA) and internal transcriber spacer (ITS) were the most used markers for identifying Leishmania species. The current study provides valuable data to encourage and direct researchers as well as public health managers in the comprehensive leishmaniasis control and prevention planning in Iran.